Stakeholder Barriers and Benefits Associated With Improving Livestock Husbandry to Prevent Jaguar and Puma Depredation. Issue 3 (4th May 2017) - Amit, Ronit; Jacobson, Susan K.
ABSTRACT: Motivating ranchers to adopt preventive husbandry practices that limit livestock depredation by large carnivores, such as jaguars ( Panthera onca ) and pumas ( Puma concolor ), requires reducing perceived barriers and increasing benefits associated with coexistence. We assessed stakeholder perspectives on preventive practices by conducting eight focus groups consisting of ranchers, researchers, and government wildlife officers in Costa Rica using a nominal group technique to identify and rank benefits, barriers, and motivations. We identified 29 benefits, 27 positive motivations, 33 negative motivations, and 20 barriers. Common responses among stakeholders highlight the importance of economic issues, contextual factors, and external support. However, social interactions, a reactive approach to management, and personal motivations also influence rancher decision making, but tend to be ignored by researchers and wildlife officers. Nominal group rankings reveal misunderstandings and misalignment of priorities among stakeholders that should be targeted by collaborative problem-solving processes. Motivations behind prevention expose nuances of human–wildlife conflict.